EFEKTIVITAS PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN REMAJA TENTANG PENANGANAN DISLOKASI - Metilda; M. Deri Ramadhan; Intan Firdaus Fauziah; Chelsy Andarini; Rasti Amelia Putri; Maisya Rizki Maulinda; Zahra Salsabila M.Noor; Putri Melati; Muhamad Rizki Andriana; N.Windy Noviandini Alya.P; Rahma Sani Rahayu (Jurnal LENTERA, 2026)
Dislocation is a musculoskeletal injury that often occurs in adolescents with high physical activity and can cause functional impairment and serious complications if not treated properly. Lack of knowledge about early recognition and first aid for dislocations often leads to delayed and inappropriate treatment. This study aims to evaluate the effectiveness of health education in improving adolescents' knowledge about managing dislocations. A quantitative descriptive study with a pre-test and post-test design was conducted on 23 high school students at Al Bidayah Batujajar. The health education intervention was delivered through lectures, interactive discussions, simulations, and the use of print and digital educational media. Data were collected using a structured questionnaire and analyzed descriptively to compare knowledge levels before and after the intervention. Findings showed a significant increase in students' knowledge after the educationalintervention. The average pre-test score was 68.17, indicating a moderate level of knowledge. After the intervention, the average post-test score increased to 88%, with most participants achieving a high level of knowledge. Health education significantly improved adolescents' knowledge about dislocations and first aid. School-based educational interventions are an effective strategy for improving musculoskeletal health literacy and can contribute to the prevention of complications related to dislocations among adolescents. asi kesehatan muskuloskeletal dan dapat berkontribusi pada pencegahan komplikasi yang terkait dengan dislokasi di kalangan remaja.